Mindfulness Training Enhances Endurance Performance and Executive Functions in Athletes: An Event-Related Potential Study. (28th August 2020) - Nien, Jui-Ti; Wu, Chih-Han; Yang, Kao-Teng; Cho, Yu-Min; Chu, Chien-Heng; Chang, Yu-Kai; Zhou, Chenglin
Abstract : Mindfulness interventions have been linked to improved sport performance and executive functions; however, few studies have explored the effects of mindfulness on sport performance and executive functions simultaneously. This study sought to examine whether a mindfulness training program would affect both the endurance performance and executive functions of athletes. In addition, event-related potentials (ERPs) associated with the Stroop task were assessed to investigate the potential electrophysiological activation associated with the mindfulness training. Applying a quasiexperimental design, forty-six university athletes were recruited and assigned into a five-week mindfulness training program or a waiting list control group. For each participant, the mindfulness level, endurance performance assessed by a graded exercise test, executive functions assessed via Stroop task, and N2 component of ERPs were measured prior to and following the 5-week intervention. After adjusting for the preintervention scores as a covariate, it was found that the postintervention mindfulness level, exhaustion time, and Stroop task accuracy scores, regardless of task condition, of the mindfulness group were higher than those of the control group. The mindfulness group also exhibited a smaller N2 amplitude than the control group. These results suggest that the five-week mindfulness program can enhance the mindfulness level, endurance performance, and multiple cognitive functions, including executive functions, of university athletes. Mindfulness training may also reduce conflict monitoring in neural processes.